The ability of mucoadhesive gingival patch loaded with EGCG on IL-6 and IL-10 expression in periodontitis - Dur M. Lashari; Mohammed Ahmed Aljunaid; Rini Devijanti Ridwan; Indeswati Diyatri; Yasmeen Lashari; Huda Qaid; Meircurius Dwi Condro Surboyo (Journal of Oral Biology and Craniofacial Research)
Objectives: The mucoadhesive gingival patch is a topical drug delivery process it does not cause any irritation in the mucosa. EGCG (Epigallocatechin-3-gallate) it has potent antioxidant, antiangiogenic and antitumor effects. The present study investigates the ability of mucoadhesive gingival patch loaded with EGCG on periodontitis and its impact on IL-6 and IL-10 expression. Method: Periodontitis model was developed in Wistar rat by induction of Porphyromonas gingivalis. Application of mucoadhesive gingival patch loaded with EGCG (GP-EGCG), mucoadhesive gingival patch loaded with doxycycline (GP-doxy) and blank patch, was done for treated periodontitis 1 h each day during 21 days. Indirect immunohistochemical analysis of IL-6 and IL-10 expressions were analyzed in the mandibular preparation of the anterior incisive region of animal. Results: The GP-EGCG treatment for 3 days until 21 days, consistently increased the IL-10 expression in periodontitis (p < 0.05). In other hand, GP-EGCG treatment lowered the IL-6 expression after 7, 14 and 21 days (p < 0.05). Conclusion: The GP-EGCG is promising for the periodontitis treatment by interfere the IL-6 and IL-10 expression.